BUNDLING POWER: A STRATEGY TO INCREASE SALES VOLUME IN A COMPETITIVE MARKET AT INDOMARET - Mutia Nurul Apriza; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
The purpose of the study was to determine the effect of product, price, promotion and place on Purchasing Decisions at Indomaret Simpang Kandis Bengkulu. Data collection using questionnaires to 95 people who shop at Indomaret Simpang Kandis. Data analysis techniques use multiple linear regression, coefficient of determination and hypothesis testing. The results showed that the product has a positive and significant influence on purchasing decisions at Indomaret Simpang Kandis area, Bengkulu city, meaning that the more product quality increases, the purchasing decisions will also increase. Price has a negative and significant effect on purchasing decisions at Indomaret Simpang Kandis area, Bengkulu city. This means that if there is an increase in price at Indomaret in the Simpang Kandis area of Bengkulu city, the purchasing decision will decrease. Promotion has a positive and significant effect on purchasing decisions at Indomaret in the Simpang Kandis area of Bengkulu city, which means that if the promotion increases, the purchasing decision will also increase. Place has a positive and significant effect on purchasing decisions, Indomaret Simpang Kandis area Bengkulu. This means that the more strategic the place, the purchasing decisions will also increase.